Fann al-Jinas wa Saja fi mandhumah al-faraid al-Bahiyah fi al-Qawaid al-Fiqhiyyah li Sayyid Abi Bakar al-Ahdaly al-Yamany as-Syafii (Dirasah Tahliliyah Baalaghiyah) - Nur Hamidah; Halimi Zuhdy (Journal of Arabic Literature (JaLi), 2021)
Nadzam is mazdzumat ilmiyah which is patterned speech that contains knowledge and normative. Changing the nadzam aims to make easier for someone to understand the knowledge and information that will be delivered. Nadzam is a literature which has high artistic value, there are beautifying elements. One of the nadzam which there are elemenys that make it beautiful is nadzamal-faraid al-bahiyah fi al-Qawaid al-Fiqhiyah creation by Sayyid Abi Bakar al-Ahdali Al-Yamani As-Syafii, that is  muhassinat lafdziyah and muhassinat maknawiyah. The purpose of this research is : 1) to know the various kinds of jinas that found in the nadzam “Al-Faraid Al-Bahiyah fi Al-Qawaid Al-Fiqhiyah” creation by Sayyid Abi Bakar al-Ahdali Al-Yamani As-Syafii; and 2) to know the various kinds of poetry contained in the nadzam “Al-Faraid Al-Bahiyah fi Al-Qawaid Al-Fiqhiyah” creation by Sayyid Abi Bakar al-Ahdali Al-Yamani As-Syafii. This research is a type of qualitative descriptive research. In collecting data, researchers used  reading and writing techniques. And for data analysis technique used by researchers in this research is by reducing data, presenting data, and conclusions. The result of this reseach are: 1) the various kinds of jinas contained in the nadzam “Al-Faraid Al-Bahiyah fi Al-Qawaid Al-Fiqhiyah” creation by Sayyid Abi Bakar al-Ahdali Al-Yamani As-Syafii is just jinas ghairu tam, there are: jinas mudhari is on 15 stanzas, jinas lahiq is on 17 stanzas, jinas marduf is on 11 stanzas, jinas mukattaf is on 7 stanzas, jinas muzayyal is on 27 stanzas, jinas muharraf is on 3 stanzas, jinas maqlub ba’du is on 1 stanzas. And in the nadzam there is also mulahhaq bi al-jinas that is isytiqaq is on 41 stanzas and syibhul isytiqaq is on 2 stanzas; and 2) various kinds of sajak which are contained in the nadzam “Al-Faraid Al-Bahiyah fi Al-Qawaid Al-Fiqhiyah” creation by Sayyid Abi Bakar al-Ahdali Al-Yamani As-Syafii is saja’ murassa’ is on 5 stanzas, saja’ mutawazi is on 129 stanzas and saja’ mutharraf is on 290 stanzas.